2021
DOI: 10.3390/cells10092231
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the FGF-FGFR Signaling System in Cancer Development and Inflammation

Abstract: For multi-cellular organisms to organize tissues, their cells must communicate with each other [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It has been widely known that the systematic inflammation response is closely related with the occurrence and development of tumors. The detailed internal mechanisms have been deeply explored and introduced in previous literatures[ 8 , 33 - 35 ]. The neutrophils, lymphocytes, platelets, monocytes and C-reactive protein are all common inflammatory biomarkers and a great number of studies have revealed the prognostic role of NLR, PLR, LMR and GPS in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely known that the systematic inflammation response is closely related with the occurrence and development of tumors. The detailed internal mechanisms have been deeply explored and introduced in previous literatures[ 8 , 33 - 35 ]. The neutrophils, lymphocytes, platelets, monocytes and C-reactive protein are all common inflammatory biomarkers and a great number of studies have revealed the prognostic role of NLR, PLR, LMR and GPS in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In mice and humans, the Fibroblast Growth Factor (FGF) family is composed of 22 polypeptides that act as secreted signaling proteins (FGF1-10, FGF16-23) or as receptor-independent intracellular factors (FGF11-14), with the latter being mainly involved in neuronal development and in regulating the electrical excitability of neurons [ 31 , 32 ]. Secreted FGFs are grouped into 6 subfamilies according to phylogenetic analysis and sequence homology.…”
Section: The Fibroblast Growth Factor (Fgf)/fgf Receptor (Fgfr) Systemmentioning
confidence: 99%
“…The subfamilies FGF1/2/5, FGF3/4/6, FGF7/10/22, FGF8/17/18, and FGF9/16/20 are known as canonical FGFs and act as local paracrine signaling molecules. The FGF19/21/23 subfamily comprises hormone-like FGFs acting as endocrine factors that control metabolic homeostasis [ 31 , 33 , 34 ]. Both canonical and hormone-like FGFs mediate their biological functions by activating cell surface tyrosine kinase (TK) receptors (FGFRs), which are encoded by four distinct genes ( FGFR1-4 ) in mammals [ 31 , 33 ].…”
Section: The Fibroblast Growth Factor (Fgf)/fgf Receptor (Fgfr) Systemmentioning
confidence: 99%
See 2 more Smart Citations